Research involving limited dependent variables: issues in the literature and recommendations for improvement - Taplin, Ross (Kluwer Academic Publishers, 2015)
Despite previous recommendations for improvement, a literature review reveals a minority of recent papers in management journals provide correct interpretations of regression coefficients for analyses of limited dependent variables. Furthermore, the use of marginal effects to interpret relationships has resulted in confusing and inaccurate conclusions. This paper recommends simpler and more informative alternatives to the calculation and reporting of marginal effects. In particular, two key recommendations involve choosing and explicitly stating a suitable measurement scale for dependent variables and explicitly stating whether relationships with independent variables are multiplicative or additive effects. These recommendations for reporting hypotheses, analysis and interpretations will not only improve the precision of future research but also provide superior interpretations of past literature. Significantly, this paper shows how standard regression coefficients can be used to interpret relationships between variables for any values of all variables. Other approaches such as the recommended inclusion of marginal effects and plots requires fixing other variables to specific values (such as their mean value) and so are of less value to readers.